2010
DOI: 10.1097/cji.0b013e3181ee6675
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumor Trafficking of GD2 Chimeric Antigen Receptor T Cells by Expression of the Chemokine Receptor CCR2b

Abstract: For adoptive T cell therapy to be effective against solid tumors, tumor-specific T cells must be able to migrate to the tumor site. One requirement for efficient migration is that the effector cells express chemokine receptors that match the chemokines produced either by tumor or tumorassociated cells. In this study, we investigated whether the tumor trafficking of activated T cells (ATCs) bearing a chimeric antigen receptor specific for the tumor antigen GD2 (GD2-CAR) could be enhanced by forced co-expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
334
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(344 citation statements)
references
References 35 publications
7
334
0
3
Order By: Relevance
“…In the future it might therefore be worthwhile to genetically modify NK cells with chemokine receptors to enhance selective tumor infiltration. That this kind of engrafted chemotaxis is beneficial was previously demonstrated by CXCR2-and CCR2-modified T cells, which showed improved tumor infiltrations and eradications in tumor xenograft models (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…In the future it might therefore be worthwhile to genetically modify NK cells with chemokine receptors to enhance selective tumor infiltration. That this kind of engrafted chemotaxis is beneficial was previously demonstrated by CXCR2-and CCR2-modified T cells, which showed improved tumor infiltrations and eradications in tumor xenograft models (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have described interesting approaches, including the chemical or enzymatic modification of the cell surface with specific adhesion molecules (45), materials engineering of artificial scaffolds and tunable matrices to direct cell adhesion and migration (46), expression or direct injection of natural homing ligands such as chemokines into sites where increased cell migration is desired (47,48), and the expression in therapeutic cells of natural receptors such as chemokine receptors whose ligands are up-regulated in inflammation or cancer (8,7,16,17). These strategies rely on naturally existing homing receptors and ligands, and they are powerful because they tap into cells' native migration axes.…”
Section: Discussionmentioning
confidence: 99%
“…The use of cells for the treatment of a growing array of diseases including cancer, autoimmunity, and chronic wounds is currently being explored (1)(2)(3)(4)(5)(6). The appropriate and efficient localization of therapeutic cells to sites of disease has been identified as an important factor for successful cell-based therapy (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, preclinical studies and clinical trials to date have shown that the homing to sites of disease of many cell types commonly used as therapeutics is frequently impaired or limited, especially after ex vivo expansion of cells in culture (7,12,18,19).…”
mentioning
confidence: 99%
“…For example, specific chemokine receptors can be ectopically expressed by T cells to improve their homing along the chemokine gradients produced by tumor cells. This approach is effective in pre-clinical models of melanoma, Hodgkin's lymphoma, and neuroblastoma in which overexpression of CXCR2, 77 CCR4 78 or CCR2b 79 by T cells enhanced their trafficking (and subsequent antitumor effects) along CXCL1, TARC and CCL2 gradients, respectively. Genetic modifications have also been exploited to counter inhibitory molecules present in the tumor microenvironment.…”
Section: -71mentioning
confidence: 99%